2022
DOI: 10.1126/science.add4250
|View full text |Cite
|
Sign up to set email alerts
|

The control of carpel determinacy pathway leads to sex determination in cucurbits

Abstract: Male and female unisexual flowers evolved from hermaphroditic ancestors, and control of flower sex is useful for plant breeding. We isolated a female-to-male sex transition mutant in melon and identified the causal gene as the carpel identity gene CRABS CLAW (CRC) . We show that the master regulator of sex determination in cucurbits, the transcription factor WIP1 whose expression orchestrates male flower development, recruits the corepressor TOPLESS to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 49 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…6A ). Recently, a new study was published that described CRABS CLAW ( CRC ), a transcription factor of the YABBY gene family controlling carpel and nectary development, in addition to flower meristem termination, as a new player in the sex determination model in melon ( Zhang et al , 2022 ). Interestingly, in our RNA-Seq data this gene was overexpressed during the GI-H episode.…”
Section: Discussionmentioning
confidence: 99%
“…6A ). Recently, a new study was published that described CRABS CLAW ( CRC ), a transcription factor of the YABBY gene family controlling carpel and nectary development, in addition to flower meristem termination, as a new player in the sex determination model in melon ( Zhang et al , 2022 ). Interestingly, in our RNA-Seq data this gene was overexpressed during the GI-H episode.…”
Section: Discussionmentioning
confidence: 99%
“…However, ongoing Y‐degeneration [ 48,49 ] may lead to eventual GSFY loss and evolution of X/A‐ratio system controlled by the number of X‐linked WUS genes. Interestingly, WUS is also involved in the sex expression pathway in kiwifruits, [ 16 ] and Cucumis , [ 50 ] implying that this mechanism possibly plays a role in gynoecium suppression of many plant groups with independently evolved dioecy and sex chromosomes. Further analyses of sub‐functionalization of GSFY or SlWUS1 and the effect of their copy numbers will allow one to test whether WUS / CLV3 ratio control the gynoecium suppression.…”
Section: Does the Wus/clv3 Balance Represent A Steppingstone In Evolu...mentioning
confidence: 99%
“…8 of a hermaphroditic melon germplasm (Wang et al 2022), and a novel sex determination gene, CmCRC , has been identified on Chr. 10 (Zhang et al, 2022). Thus, the study of the genetic mechanism of melon sex determination has much potential, and novel genes may still be discovered in melon.…”
Section: Introductionmentioning
confidence: 99%